2021
DOI: 10.1002/elsc.202100083
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Comparative molecular docking and molecular‐dynamic simulation of wild‐type‐ and mutant carboxylesterase with BTA‐hydrolase for enhanced binding to plastic

Abstract: According to the literature review, microbial degradation of polyethylene terephthalate by PETases has been detected effective and eco-friendly. However, the number of microorganisms capable of such feats is limited with some undesirable bioprospecting results. BTA-hydrolase has been already reported capable of degrading polyethylene terephthalate. Therefore, mutation by in silico sitedirected mutagenesis means to introduce current isomer of PETase for polyethylene terephthalate degradative capability as a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…On the other hand, site-directed mutagenesis is also used to alter the activity of genes associated with microplastic degradation. In a recent study, Lameh et al ( 2022 ) reported mutation of carboxylesterase by in silico site‐directed mutagenesis to produce BTA‐hydrolase in Archaeoglobus fulgidus to enhance its ability to degrade polyethylene terephthalate.…”
Section: Modern Biotechnological Methods To Enhance Microplastic Degr...mentioning
confidence: 99%
“…On the other hand, site-directed mutagenesis is also used to alter the activity of genes associated with microplastic degradation. In a recent study, Lameh et al ( 2022 ) reported mutation of carboxylesterase by in silico site‐directed mutagenesis to produce BTA‐hydrolase in Archaeoglobus fulgidus to enhance its ability to degrade polyethylene terephthalate.…”
Section: Modern Biotechnological Methods To Enhance Microplastic Degr...mentioning
confidence: 99%
“…The polar hydrogen atoms and Gasteiger charges were added to the protein chain 19 . The ligands were subjected to the same procedure to ensure that the torsions for rotation were accurately adopted during docking 20 . The macromolecules were under rigid conditions when interacting with the ligand under flexible conditions, using the Lamarckian Genetic Algorithm (LGA) method 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Energy minimization techniques were applied to optimize the ligand conformation and lower its energy state, ensuring it was in a suitable form for subsequent molecular docking experiments. [ 10 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%